Divine Rulers in a Secular State - Kallinen, Timo (Studia Fennica Anthropologica, 2016)
The divine kingship and chiefship of the Asante people of central Ghana have been undergoing a shift towards secularization since the start of the colonial era. Timo Kallinen maintains that a close examination of this transformation provides us with a better understanding of secularization processes in Ghana more broadly, and in other post-colonial societies whose historical development likewise differs from that of the modern West, and which have largely confronted secular modernity through encounters with European colonialism. roughout the volume secularization is understood as a process in modern society whereby divinity is separated from the ways in which both human society is regulated and physical nature is understood to function.